A nutrient control on marine anoxia during the end-Permian mass extinction - Schobben, M; Foster, WJ; Sleveland, ARN; Zuchuat, V; Svensen, HH; Planke, S; Bond, DPG; Marcelis, F; Newton, RJ; Wignall, PB; Poulton, S (Nature Research, 2020)
Oxygen deprivation and hydrogen sulfide toxicity are considered potent kill mechanisms during the mass extinction just before the Permian–Triassic boundary (~251.9 million years ago). However, the mechanism that drove vast stretches of the ocean to an anoxic state is unclear. Here, we present palaeoredox and phosphorus speciation data for a marine bathymetric transect from Svalbard. This shows that, before the extinction, enhanced weathering driven by Siberian Traps volcanism increased the influx of phosphorus, thus enhancing marine primary productivity and oxygen depletion in proximal shelf settings. However, this non-sulfidic state efficiently sequestered phosphorus in the sediment in association with iron minerals, thus restricting the intensity and spatial extent of oxygen-depleted waters. The collapse of vegetation on land immediately before the marine extinction changed the relative weathering influx of iron and sulfate. The resulting transition to euxinic (sulfidic) conditions led to enhanced remobilization of bioavailable phosphorus, initiating a feedback that caused the spread of anoxic waters across large portions of the shelf. This reconciles a lag of >0.3 million years between the onset of enhanced weathering and the development of widespread, but geographically variable, ocean anoxia, with major implications for extinction selectivity.